2011
DOI: 10.3397/1.3630002
|View full text |Cite
|
Sign up to set email alerts
|

Update of an alternative analysis of sleep awakening data

Abstract: Airport and airspace planners need a reliable method for quantifying the effects of nighttime operations on communities. Research has shown that cumulative metrics such as Lnight, Ldn and Lden show little or no correlation with aircraft noise event (ANE) produced awakenings. What is needed is a reliable method for quantifying the likely awakenings that will result from a full night of aircraft operations. This paper reports the results of an update of the analysis reported previously in Noise Control Engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Fidell et al (2010) note that the mean assumed sensitivity of test subjects at Denver International Airport (in logit-scaled units, M ¼ À0.09, SE ¼ 0.03) was far greater and significantly higher (F 2,136 ¼ 395.6, p < 0.001, g 2 ¼ 0.28, with 95% confidence limits from 0.22 to 0.34) than at Los Angeles International Airport (M ¼ À0.97, SE ¼ 0.02) and at Castle Air Force Base (M ¼ À0.95, SE ¼ 0.02). Miller et al (2011) report further differences between the mean sensitivities to awakening of individuals at Schiphol Airport and those at the other airports.…”
Section: Anderson and Millermentioning
confidence: 73%
See 4 more Smart Citations
“…Fidell et al (2010) note that the mean assumed sensitivity of test subjects at Denver International Airport (in logit-scaled units, M ¼ À0.09, SE ¼ 0.03) was far greater and significantly higher (F 2,136 ¼ 395.6, p < 0.001, g 2 ¼ 0.28, with 95% confidence limits from 0.22 to 0.34) than at Los Angeles International Airport (M ¼ À0.97, SE ¼ 0.02) and at Castle Air Force Base (M ¼ À0.95, SE ¼ 0.02). Miller et al (2011) report further differences between the mean sensitivities to awakening of individuals at Schiphol Airport and those at the other airports.…”
Section: Anderson and Millermentioning
confidence: 73%
“…More recently, Anderson and Miller (2007), ANSI (2008, Part 6), and Miller et al (2011) have suggested other methods for predicting sleep disturbance from what little field information is available. Figure 1 compares three fitting functions suggested for predicting the percentage of people awakened by noise intrusions into residential sleeping quarters from absolute indoor SEL values.…”
Section: Differences Among Awakening Prediction Methodsmentioning
confidence: 98%
See 3 more Smart Citations